Development of HiBiT-Tagged Recombinant Infectious Bronchitis Coronavirus for Efficient in vitro and in vivo Viral Quantification - Liang, Xiao Ying; Zhu, Qing Chun; Liang, Jia Qi; Liu, Si Ying; Liu, Ding Xiang; Fung, To Sing (Frontiers in Microbiology, 2020)
Coronaviruses (CoVs) are enveloped (+) ssRNA viruses of veterinary and medical importance. Because recombinant CoVs with reporter proteins fused with viral proteins are usually non-viable or unstable, a small and quantifiable epitope tag would be beneficial to CoV research. In this study, we integrated the NanoLuc Binary Technology to the reverse genetics of infectious bronchitis virus (IBV), a prototypic gammacoronavirus. The 11-amino-acid HiBiT tag was inserted to the spike (S) or membrane (M) protein, and the recombinant IBVs (rS-HiBiT and rM-HiBiT) were characterized. Compared with the rIBV-p65 control, rS-HiBiT exhibited comparable growth kinetics, whereas rM-HiBiT replicated slightly slower. The levels of HiBiT-tagged S and M proteins in the infected cells or the culture supernatant could be both rapidly (~15 min) and efficiently (30 μL sample volume) determined using the HiBiT luminescence assay. Notably, replication of the HiBiT-tagged IBV could be monitored continuously in an infected chicken embryo, and rS-HiBiT was genetically stable for at least 20 passages. By integrating the HiBiT tagging system with CoV reverse genetics, this new reporter system may facilitate future study of CoV replication and pathogenesis.